Factors Identification of Rising a Resilience among Single Mother: A Case Study in Felda Chini and Felda Jengka, Pahang, Malaysia - Lukman@Zawawi, Mohamad; Normala, Riza; Azlini, Chik (2018)
Single mothers has been recognized as a challenging role, with difficulties including low monetary and poor psychological health. Developing resilience may authorize single mothers to face the challenges whilst leading psychologically healthy and productive lives. This study focuses on the factors that influence Malay single mother’s resilience in Felda Chini and Felda Jengka. The data acquired from the respondents were analyzed using the pivot table in Microsoft Excel to get the percentage and frequency. Finally, the results of the analysis show that there are five factors that can influence the rise of the resilience of Malay single mothers in the area of the study. The five factors are future planning, relationship with family members, self-perceptions, social resources, and lifestyle structures.